Antimicrobial activity of aqueous Quercus infectoria gall extract against pathogenic Leptospira - Mustafa, Husna (Universiti Sains Malaysia, 2016)
Leptospirosis is a bacterial zoonotic infectious disease that occurs worldwide caused by Leptospira and transmitted to human through direct or indirect contact with the urine of infected animal. Quercus infectoria gall extract is known to have a broad spectrum antimicrobial activity in-vitro. This study was conducted to determine the antimicrobial activity of Q. infectoria gall extract against pathogenic Leptospira and to evaluate the morphological changes of extract-treated cells using scanning electron microscope (SEM). Two-fold serial microdilution broth assay was used to determine the minimum inhibitory concentration (MIC) of aqueous Q. infectoria gall extract against L. interrogans serovar Javanica dan L. interrogans serovar Icterohaemorhagiae at concentration ranging from 4.00 mg/mL to 0.0078 mg/mL. Minimum bactericidal concentration (MBC) was determined by sub-culturing the broth from microtitre plate well showing no apparent growth or turbidity into the freshly prepared EMJH media and observed under dark field microscope after 3 weeks incubation for growth detection. The cell morphology of extract-treated and untreated L. interrogans serovar Icterohaemorhagiae were analyzed using SEM. The results of broth microdilution assay demonstrated that aqueous Q. infectoria gall extract possessed antimicrobial activity against both L. interrogans serovar with MIC values of 0.125 mg/mL. The MBC values for L. interrogans serovar Javanica dan L. interrogans serovar Icterohaemorhagiae were 0.125 mg/mL and 0.25 mg/mL respectively. The SEM micrograph showed changes of shape and size of the L. interrogans serovar Icterohaemorrhagiae extract-treated cells (at 8x MIC) as compared to the untreated cells. In conclusion, aqueous Q. infectoria gall extract has the potential to be explored for its efficacy and use in the treatment of leptospirosis.